2022
DOI: 10.1002/macp.202200035
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Adjustment Strategy to Improve the Sensitivity of Ionogels for Flexible Sensors

Abstract: Recently, ionogels-based flexible/stretchable sensors have been receiving great attention, which greatly promotes the development of artificial flexible electronics. Except transparency, stretchability, stability, self-healing, and adhesion, the high conductivity of ionogels and high sensitivity as a sensor still are huge challenges. This work proposes a spatial adjustment strategy to improve sensitivity and conductivity through reducing the spatial hinderance without a change in the compound types and ratio. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…As indicated in Figure S16 (Supporting Information), the experimentally derived relative resistance changes versus strain curve can be fitted into a quadratic function, exhibiting very similar trend to theoretical curve. Variations in the coefficients of fitted and theoretical functions are believed to be caused primarily by systematic differences, such as materials used, [53] cross-link density, [54] and even some measurement errors. These factors would impact the sensitivity of ionogels.…”
Section: Sensing Performancementioning
confidence: 99%
“…As indicated in Figure S16 (Supporting Information), the experimentally derived relative resistance changes versus strain curve can be fitted into a quadratic function, exhibiting very similar trend to theoretical curve. Variations in the coefficients of fitted and theoretical functions are believed to be caused primarily by systematic differences, such as materials used, [53] cross-link density, [54] and even some measurement errors. These factors would impact the sensitivity of ionogels.…”
Section: Sensing Performancementioning
confidence: 99%
“…The mechanical properties of the bicontinuous ionogel and the reported ionogels are summarized in Figure f. It is found that the tensile strength, tensile strain, and toughness of the bicontinuous ionogel at the optimal formulation exceed those of most of the existing ionogels. Most importantly, the bicontinuous ionogel obtains an excellent mechanical property without compromising its conductivity (discussed later).…”
Section: Resultsmentioning
confidence: 96%
“…Self-Healing and Recyclable Properties of the Bicontinuous Ionogel. Different from the covalent crosslinked ionogels, 25,40 the bicontinuous ionogel is synthesized without any chemical cross-linkers. The interpenetrated polymer-rich phase and solvent-rich phase are predominantly governed by hydrogen bonds.…”
Section: Conductivity Of the Bicontinuous Ionogelmentioning
confidence: 99%